PENGARUH PENERAPAN AUDIT E-COMMERCE TERHADAP KINERJA AUDITOR : STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI SURABAYA, INDONESIA - Muhammad Ismail Saleh; Muhammad Wisnu Girindratama (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2021)
This study aims to identify using empirical research how the impact of E-commerce on the auditing profession. The object of this research is the auditor who works at the Public Accounting Firm (KAP) in the city of Surabaya. Data collection was done by doing a survey through a questionnaire media. The primary data generated by 60 questionnaires can be processed using Partial Least Square. Evaluation of the model in PLS is done by evaluating the outer model and inner model. The data in this study were collected through questionnaires and analyzed by using a simple linear regression model. The results of the study found that the implementation of e-audit has a positive and significant effect on auditor performance. The auditor performance is influenced by an e-audit factor of 83% and the remaining is influenced by other factors.